Irradiation of human skin by short wavelength ultraviolet radiation (100--290 nm) (u.v.C): increased concentrations of arachidonic acid and prostaglandines E2 and F2alpha. - Camp, R D (1978)
1. Human abdominal skin was irradiated with six times the minimal erythema dose of ultraviolet C (100--290 nm) radiation. Erythema appeared at 3 h, was of moderate degree by 6 h and was maximal at 12--24 h. It was reduced at 48 h and by 72 h had disappeared. 2. A suction bulla technique was used for the recovery of exudate from normal and inflamed skin at 6, 18, 24 and 48 h after irradiation. 3. Prostaglandin-like activity, estimated by bioassay, showed maximum increase at 18 h, when erythema was also maximum. PGF 2alpha, measured by both radioimmunoassay and by combined gas-liquid chromatography--gas spectrometry, followed a similar time course then fell to normal, or near normal, levels at 48 h. 4. Prostaglandin E2 and arachidonic acid concentrations, measured by gas chromatography--mass spectrometry, were maximally raised at 18--24 h. At 48 h, when some erythema was still present, though reduced, prostaglandin E2 concentrations were still raised above control values. 5. The results provide direct evidence in support of the view that the erythma following irradiation of human skin by u.v.C involves activation of arachidonic acid metabolism. However, the relationship between the erythema and increased prostaglandin activity is not fully understood.